Possibility of Herbal Tea Production from Corn Silk (Zea mays) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Corn silk is usually discarded as waste. It has a great medicinal importance due to the presence of valuable bioactive phytochemical compounds. It’s believed to be nontoxic and safe for human. Among various parts of corn, the corn silk is a rich source of antioxidant components and possesses strong antioxidant potential. It could be utilized as herbal tea like a healthy beverage. Objective of this study focused on the effect of blanching temperature and time; vacuum drying temperature and pressure to anthocyanin (mg/L), flavonoid (µg RE/g) and overall acceptance (sensory score) of the dried corn silk tea. Results showed that corn silk should be blanched in hot water 95oC at 10 seconds in the present of CaCl2 1.5% and then being dried by vacuum dryer at 45oC, -0.8 bar for 4 hours to get the final moisture content 8% available for preservation. It’s considered as a suitable raw material for production of functional food.Keywords: Corn silk, Blanching, Vacuum drying, Herbal tea, Anthocyanin, Flavonoid.